Β-Cypermethrin and its metabolite 3-phenoxybenzoic acid exhibit immunotoxicity in murine macrophages. (11th October 2017) - Wang, Xia; He, Bingnan; Kong, Baida; Wei, Lai; Wang, Rong; Zhou, Chenqian; Shao, Yiyan; Lin, Jiajia; Jin, Yuanxiang; Fu, Zhengwei
Abstract: β-Cypermethrin (β-CYP), one of most important pyrethroids, is widely used to control insects, and has been detected in organisms, including human. Pyrethroids have been shown to pose neurotoxicity, hepatotoxicity, endocrine disruption and reproductive risks in mammals. However, research in immunotoxicity of pyrethroids, especially their metabolites, is limited. A common metabolite of pyrethroids is 3-phenoxybenzoic acid (3-PBA) in mammals. Thus, in this study, we evaluated the immunotoxicity of β-CYP and 3-PBA in mouse macrophages, RAW 264.7 cells. MTT assays showed that both β-CYP and 3-PBA reduced cell viability in a concentration- and time-dependent manner. Flow cytometry with Annexin-V/PI staining demonstrated that both β-CYP and 3-PBA induced RAW 264.7 cell apoptosis. Furthermore, our results also showed that N -acetylcysteine partially blocked β-CYP- and 3-PBA-induced cytotoxicity and apoptosis. Intrinsic apoptotic pathway was stimulated by both β-CYP and 3-PBA exposure. In addition, we found that β-CYP and 3-PBA inhibited mRNA levels of pro-inflammatory cytokines with or without LPS stimulation. Phagocytosis assay showed that both β-CYP and 3-PBA inhibited phagocytic ability of macrophages. Moreover, it was also found that both β-CYP and 3-PBA increased reactive oxygen species (ROS) levels in RAW 264.7 cells. Accordingly, both β-CYP and 3-PBA were found to regulate the mRNA levels of oxidative stress-related genes in RAW 264.7 cells. Taken together, the results obtained in this study demonstrated that β-CYP and 3-PBA may have immunotoxic effect on macrophages and that elevated ROS may underlie the mechanism. The present study will help to understand the health risks caused by β-CYP and other pyrethroids.